2011
DOI: 10.3109/08039488.2011.598556
|View full text |Cite
|
Sign up to set email alerts
|

The influence of therapeutic alliance and insight on medication adherence in schizophrenia

Abstract: A weak therapeutic alliance and low insight are associated with poor adherence in patients with schizophrenia or schizoaffective disorder who were hospitalized. Specific psycho-educational programs to improve therapeutic alliance and insight should be implemented to achieve better therapeutic adherence and outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 43 publications
6
54
0
Order By: Relevance
“…Participants who used alcohol and cannabis were four to five times more likely to be non-adherent than those who didn't used. This finding coincides with study done in France which reported non adherence was associated in patients with substance use [24]. Possible reasons includes the specified substance use can have negative impacts on a person's internal state causing increased cognitive anomalies and unpleasant withdrawal symptoms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Participants who used alcohol and cannabis were four to five times more likely to be non-adherent than those who didn't used. This finding coincides with study done in France which reported non adherence was associated in patients with substance use [24]. Possible reasons includes the specified substance use can have negative impacts on a person's internal state causing increased cognitive anomalies and unpleasant withdrawal symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…Amanuel mental specialized hospital is the only mental hospital in the country which engaged in giving core mental clinical services, conducting research and trainings of professionals. There were about 41,583 schizophrenia patient who had regular follow in the year 2012 at outpatient; the majority are male (24,154). The hospital has 300 beds in 11 case teams (wards) which serves patient from the whole country.…”
Section: Study Design and Subjectmentioning
confidence: 99%
“…A need for more prospective and intervention studies was identified. Patients with a lack of insight into their psychiatric disorder have also been found to be at risk of nonadherence [13]. These studies demonstrate that motivational factors extend beyond knowledge of medication efficacy and adverse effects.…”
Section: Determinants Of Nonadherencementioning
confidence: 99%
“…Some studies indicate, for instance, that a weak therapeutic alliance and low insight might be related to poor adherence in patients with schizophrenia. [42] Another study by Spiekermann et al [43] stated that patients with schizophrenia who had stronger cognitive impairments showed lower adherence behavior compared to those without cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%